PENDIDIKAN KESEHATAN PENCEGAHAN SKABIES DI PONDOK PESANTREN AL-ARIFIN - Henri Setiawan; Heri Ariyanto; Fidya Anisa Firdaus; Refi Nantia Khairunisa (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Scabies is a skin disease caused by investment and sensitivity by Sarcoptes scabei mites, often found in Islamic boarding schools, because of the place was humid and the students' knowledge about life style was lack. Health Education was intended to increase the knowledge of the students at Al-Arifin Islamic boarding school about scabies and how to prevent it. The method of implementation in this community service activities was started from planning, assessment, implementation, and evaluation. Health education was carried out through lectures and discussion by leaflets and PowerPoint presentations. The results showed 70.00% of participants gave an excellent rating of health education. Scabies health education activities provide benefits to improve health degree of public health specifically in the boarding school environment. Health education about scabies in the boarding school environment was very useful for increasing the knowledge of the students.